Profit Growth of The Company: An Empirical Examination of Its Determining Factors - Santoso, Aprih; Ophilia , Karisma (Journal of Business and Political Economy : Biannual Review of The Indonesian Economy, 2021)
The agricultural sector is experiencing difficulties in terms of decreased corporate profits. The average profit growth in 2014 was 487, decreased in 2015 by 364, then increased in 2016 by 653, and decreased from 2016-2019. The decline in profit occurred due to the abundant production of agricultural products, and not infrequently, some agricultural commodities were barely produced due to crop failure. This study examines the effect of Current Ratio (CR), Net Profit Margin (NPM), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) on profit growth in agriculture sector companies listed on the IDX in 2014-2019. This research uses quantitative data with multiple linear regression techniques. The research sample was determined by purposive sampling technique. Quantitative analysis includes classic assumption tests (normality test, multicollinearity test, heteroscedasticity test, autocorrelation test), multiple linear regression test, model feasibility test through t-test, F-test, and coefficient of determination. The results showed that Current Ratio (CR), Debt to Equity Ratio (DER), and Total Asset Turnover (TATO) did not affect profit growth in agricultural companies listed on the Indonesia Stock Exchange (BEI) in 2014-2019, but Net Profit Margin (NPM) affect profit growth in agricultural companies listed on the Indonesia Stock Exchange (BEI) in 2014-2019. The contribution of the results of this study can support the conception of signal theory (Signaling theory), which suggests the importance of information issued by companies to investment decisions. Information is essential for investors and businesspeople because information provides information on records and descriptions of the past, present and future for companies and the capital market. Keywords: Current Ratio, Debt, Asset, Margin, Profit. JEL Classification: G39, G19, Q02